Estratégias para o manejo de Carapa guianensis Aublet na Floresta Nacional do Tapajós - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The objectives of this thesis were to analyze the population structure and spatial pattern of Carapa guianensis Aublet trees and to define its Minimum Logging Diameter (MLD) and Cutting Cycle (CC) in the Tapajós National Forest, to prospect timber management strategies for that species. The data to answer the first objective comes from the 100% (pre-exploratory) inventory of Annual Production Units (APUs) 4, 9, 10, 11, 12, 13 and 1, with inclusion level of diameter at breast height – DBH ≥ 20 cm. The horizontal structure, diameter distribution, the spatial distribution pattern using Ripley's K method and the Kernel density for the total population and by diameter class were calculated, taking into account the geographic coordinates of the trees. The spatial distribution pattern was predominantly aggregated, being essential for the planning and execution of timber and non-timber harvesting activities for possible future management of the species. Kernel density maps proved to be an effective tool in the capacity to provide subsidies for the manager to plan both the timber exploitation ofCarapa guianensis and non-timber exploitation. To respond to the second objective, 30 trees were selected, located in APUs 4 and 10 in the Tapajós National Forest. Using a probe, 2 to 3 wood cores per tree were collected at a height of 1.3 m above the ground, totaling 85 cores. To model growth, the Growth-Oriented Logging (GOL) method was applied, with the construction of curves of diameter, basal area, and volume as a function of age. The value of the current annual increment (CAI) and the mean annual increment (MAI) of the DBH of the trees without the bark were obtained from the cumulative growth in the different years. The MLD corresponded to the diameter at the age at which the species reached its highest current increase in volume. The cutting cycle was determined by estimating the average passage time through the 10 cm diameter classes, until reaching the calculated specific MLD. The species Carapa guianensis has distinct annual growth rings, that allow modeling the growth patterns in diameter, volume and basal area, allowing specific management criteria to be established. The results indicate that in order to have sustainable management, the MLD must be 50 cm, with a 14,8-year cutting cycle.
Keywords: Estrutura Populacional; Dendrocronologia; Incremento; CNPQ:: CIENCIAS AMBIENTAIS; Impactos Ambientais e Sociais da Mudança do Uso da Terra na Amazônia